Strategi Penerapan Flexible Working Arrangement Di Masa Pandemi Covid-19 Pada Biro Kepegawaian Dan Organisasi Kementerian Perhubungan - Marina Marina; Marini Bekti Noviati; Nurbaeti Nurbaeti; Irma Wati; Sugeng Santoso (Universitas Mercu Buana, 2021)
This study aims to analyze the strategy for implementing flexible working arrangements at the Bureau of Personnel and Organization of the Ministry of Transportation during the Covid-19 pandemic. The research method used is a mixed method design approach. The type of data used in this study is primary data that comes from interviews and filling out questionnaires, observations, documentation and is also supported by secondary data obtained from websites and related archives that can be accessed. This research was conducted at the Bureau of Personnel and Organization of the Ministry of Transportation. In this study, 85 employees participated in filling out questionnaires that were distributed.